1995
DOI: 10.1007/bf02286400
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen turnover on organic and conventional mixed farms

Abstract: Separate focus on crop fertilization or feeding practices inadequately describes nitrogen (N) loss from mixed dairy farms because of (1) interaction between animal and crop production and between the production system and the manager, and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 14 publications
4
42
1
1
Order By: Relevance
“…Therefore, we find that these are conservative estimates and it seems therefore reasonable to use these estimates to assess differences in the emissions also. The findings were in agreement with studies on Danish pilot farms (Halberg et al, 1995;Halberg, 1999;Nielsen and Kristensen, 2005).…”
Section: Methodology: Establishment Of Farm Typessupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, we find that these are conservative estimates and it seems therefore reasonable to use these estimates to assess differences in the emissions also. The findings were in agreement with studies on Danish pilot farms (Halberg et al, 1995;Halberg, 1999;Nielsen and Kristensen, 2005).…”
Section: Methodology: Establishment Of Farm Typessupporting
confidence: 92%
“…For each of the 31 farm types, N and P balances were established at farm gate level, herd level and field level following the procedures of Halberg et al (1995) and Kristensen et al (2005a). The N input to the farm types included: feed concentrates, straw, artificial fertilizer, manure, deposition, biological N fixation (BNF) and living animals.…”
Section: Modelling Farm Nutrient Balances and Emissionsmentioning
confidence: 99%
“…Calculations demonstrate that the systemic effect of organic agriculture in both cattle and pig production has great implication on the nutrient balance and the balance-surplus in relation to the product (Haas, 1995;Halberg et al, 1995;Martinson, 1998;Sundrum & Trangolao, 2000). There is reason for the assumption that the benefit of the system-related approach on minimising pollution are much more effective as compared to management-related factors, such as increasing animal performance per animal per year.…”
Section: Prevention Strategymentioning
confidence: 99%
“…In contrast, in Germany, both Finckh et al [116] and Möller et al [117] found that NUE can be improved under low input or organic potato production systems, possibly linked to improved crop light use efficiency when N is limiting. Halberg [110] and Halberg et al [118] found significantly higher NUE in organic versus conventional dairy farms and lower N surplus per hectare. Askegaard et al [31] and Halberg [110] demonstrated a high NUE from supplemental spring applied manure (when applied at a moderate rate of 70 kg N/ha) with no added N leaching.…”
Section: Nitrogenmentioning
confidence: 99%